2003
DOI: 10.1021/jf034646x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Biodegradable Films Made from Wheat Gluten Protein Fractions

Abstract: Gliadins and glutenins were extracted from commercial wheat gluten on the basis of their extractability in ethanol and used to produce film-forming solutions. Films cast using these gliadin- and glutenin-rich solutions were characterized. Glycerol was used as a plasticizer, and its effect on the films was also studied. Films obtained from the glutenin fraction presented higher tensile strength values and lower elongation at break and water vapor permeability values than gliadin films. Gliadin films disintegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 29 publications
6
63
0
Order By: Relevance
“…Generally, starch based films turn out to be more hydrophilic with an increase in plasticizer concentration. Thus, several investigations reported that the moisture content of hydrocolloid films increases by adding more plasticizer (Ghasemlou et al 2011;Hernández-Munoz et al 2003;Kristo and Biliaderis 2006;Zhang and Han 2006). However, the effect of sorbitol on the moisture content of SPS films was not obvious as that of Gand GS-plasticized films.…”
Section: Film Moisture Contentmentioning
confidence: 99%
“…Generally, starch based films turn out to be more hydrophilic with an increase in plasticizer concentration. Thus, several investigations reported that the moisture content of hydrocolloid films increases by adding more plasticizer (Ghasemlou et al 2011;Hernández-Munoz et al 2003;Kristo and Biliaderis 2006;Zhang and Han 2006). However, the effect of sorbitol on the moisture content of SPS films was not obvious as that of Gand GS-plasticized films.…”
Section: Film Moisture Contentmentioning
confidence: 99%
“…25 WG is a protein blend consisting of two main components: gliadin (monomeric protein) and glutenin (polymeric protein). Gliadin contributes mainly to the viscous behavior of the material, while glutenin influences mainly the elasticity 18,26 . Typically, the pristine WG has no regular self-assembled structure, but denatured aggregates can develop at an elevated temperature, especially in the presence of glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Water molecules prefer to cluster with each other in foods with high water content (Avital et al 1990;Hernaandez-Munz et al 2003). Water clustering is one mechanism proposed to interpret the sharp upturn in an isotherm curve.…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterize clustering in waterpolymer mixture, many qualitative or quantitative approaches have been developed, including thermodynamic analysis, Park isotherm model (Chun and Lee 2015), Brown model, Zimm-Lundberg theory, Flory-Huggins theory and engaged species induced clustering (ENSIC) model (Chu et al 2006). In food research, the ZimmLundberg approach was used in several reports (Avital et al 1990;Carrillo et al 1988;Hernaandez-Munz et al 2003).…”
Section: Introductionmentioning
confidence: 99%